Kinship System and Customary Government of the Waropen Indigenous Community - Tanati, Daniel (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
This study aims to determine the kinship system and customary government of the Waropen indigenous community. The research method used is empirical by observing the reality that occurs in the field. The results of this study reveal that the Waropen indigenous community recognizes a local kinship group called "da". Almost all villages in Waropen have three to five "da" which oversee several bawa houses (large and long houses). Family members feel bound by kinship ties that are calculated through the male line. Members of the "da" believe that they come from the same ancestors, although they are often unable to explain these kinship relationships concretely. In Waropen society, larger kinship groups are formed by "ruma bawa" which has two meanings, namely: (1) patrilocal extended family and (2) house as a place to live. Waropen society also recognizes local kinship groups. Its members are bound by kinship ties that are calculated through the father's line (patrilineal). In the customary government system of the Waropen indigenous community, several positions are known in the customary structure, which also provide clues about the boundaries of social stratification. These positions are: Sera Bawa, Mosaba, (Pertuan/ruler/King), Eso (Commander), Rubasa (People's Deputy), Manobawa, Sera-Titibi (Pertuan for groups in small circles/keret) Waribo, and Ghoinino.